Modern challenges to the legal examination regulations - Кіцен, Наталія Валентинівна; Кіцен, Н. В.; Кицен, Наталия Валентиновна; Kitsen, Nataliia V.; Факас, Ілона Борисівна; Факас, І. Б.; Факас, Илона Борисовна; Fakas, Ilona B.; Бабій, Алла Юріївна; Бабій, А. Ю.; Бабий, Алла Юрьевна; Babii, Alla Y. (Editorial Primmate S. A. S., 2020)
The article is devoted to the consideration of problems of legal expert examination of legal acts. One of the criteria for the effectiveness of a normative legal act as a basic element of legislation is its legal correctness. The dramatic changes that have taken place in Ukraine in recent years have significantly increased the role of legal means and mechanisms in the social and political life of the country. The effectiveness of transformations in the country aimed at forming civil society and the rule of law, strengthening the law and order depends on the perfection of the existing legal acts, their projects and the adoption of correct and legally justified decisions. Ensuring compliance with this criterion avoids inconsistencies in legislation and, as a consequence, ensures the unity of legal space. That is why legal expertise is a full-fledged tool for ensuring legal correctness and overcoming rulemaking, which requires a comprehensive analysis and comprehensive examination of the essence of legal expertise in the mechanism of legal regulation. The tasks that need to be addressed in the process of research on this issue can be attributed to: the study of the concept and features of legal expertise of draft normative legal acts, both in the legal literature, and the current and prospective legislation of Ukraine.

Статтю присвячено розгляду проблем проведення правової експертизи нормативно-правових актів. Одним із критеріїв ефективності нормативного правового акту як основного елементу законодавства є його правова коректність. Кардинальні зміни, які відбулися в Україні за останні роки, значно підвищили роль правових засобів і механізмів в суспільно політичному та економічному житті країни. Ефективність здійснюваних в країні перетворень, направлених на формування громадянського суспільства та правової держави, зміцнення законності і правопорядку, залежить від того, наскільки досконалими є діючі нормативно-правові акти, їх проекти та ухвалюються правильні і обґрунтовані з правової точки зору рішення. Забезпечення відповідності даним критерієм дозволяє уникнути неузгодженості у законодавстві, і, як наслідок, забезпечити єдність правового простору. Саме тому правова експертиза є повноцінним інструментом забезпечення правової коректності та подолання нормотворчих помилок, який потребує комплексного аналізу та усестороннього дослідження сутності правової експертизи в механізмі правового регулювання. До завдань, що потребують свого вирішення в процесі дослідження цього питання можна віднести: дослідження поняття та ознак правової експертизи проектів нормативно правових актів, як у юридичній літературі, так і чинному та перспективному законодавстві України.
Kitsen N. Modern challenges to the legal examination regulations / N. Kitsen, I. Fakas, A. Babii // Amazonia Investiga. – Vol. 9. – Iss. 28. – Editorial Primmate S. A. S., 2020. – P. 22-29.
Keywords: legal expertise; regulations; mechanism of legal regulation; improvement of legislation; expert support for lawmaking; правова експертиза; нормативно-правові акти; механізм правового регулювання; вдосконалення законодавства; експертне забезпечення правотворчості; Research Subject Categories::LAW/JURISPRUDENCE